Flatness-Based Control of Parallel Inverters in a Microgrid - GHOUINI Mohammed Nadhir; MEDJDEN Abdelsabour Zakaria; BENALIA Atallah (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electrotechnique, 2024)
Globally, the push toward eco-friendly energy solutions is growing, highlighting the pivotal role of micro-grid technology in facilitating renewable energy integration. This dissertation concentrates on a critical element of AC micro-grid management—specifically, the control of inverters. The main objective of this dissertation is to enhance power quality, enable effective load sharing, and manage circulating currents, to address these challenges, a one-loop, flatness- based control strategy is proposed for the management of a single inverter and multiple inverters in parallel. This control strategy capitalizes on the advantage of state and input variables that can be directly expressed through flat outputs and their derivatives, facilitating precise trajectory generation. This approach notably leverages the inherent advantages of flatness to improve system response and operational efficacy. The study presented in this dissertation could significantly contribute to the fields of micro-grid management and sustainable energy practices.
Automatic and systems